Awesome entertainment records - Kallen, Stuart A., 1955- (Edina, Minn. : Abdo & Daughters ; Minneapolis, Minn. : Distributed by Rockbottom Books, 1991)
Presents world records in the entertainment field, including the largest movie set ever built and the most frequently sung song in the English language.
Cover title: Awesome entertainment.
Keywords: Performing arts -- Miscellanea -- Juvenile literature; World records -- Juvenile literature; Performing arts -- Miscellanea; World records